One Hundred Consecutive Minimally Invasive Parathyroid Explorations - Udelsman, Robert (2000)
OBJECTIVE: To review the outcomes of 100 consecutive minimally invasive parathyroid explorations. SUMMARY BACKGROUND DATA: Minimally invasive parathyroidectomy (MIP) has challenged the traditional approach of bilateral neck exploration for patients with primary hyperparathyroidism. Most patients with primary hyperparathyroidism have a single adenoma that when resected results in cure. It therefore appears logical to perform a directed approach to adenoma extirpation. MIP involves high-quality sestamibi images obtained with single photon emission computed tomography to localize enlarged parathyroid glands in three dimensions, limited exploration after surgeon-administered cervical block anesthesia, rapid intraoperative parathyroid hormone assay to confirm the adequacy of resection, and discharge within 1 to 3 hours of surgery. METHODS: MIP was offered to 100 selected consecutive patients during an 18-month period beginning in March 1998. RESULTS: Ninety-two cases were accomplished under cervical block anesthesia and 89 of these on an ambulatory basis. The cure rate was 100%, and there were no long-term complications. The mean hospital charge for MIP was less than 40% of that associated with traditional exploration. CONCLUSIONS: Outpatient MIP appears to be the procedure of choice for most patients with primary hyperparathyroidism.